2012
DOI: 10.1016/j.ydbio.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosome inactivation in monkey embryos and pluripotent stem cells

Abstract: Inactivation of one X chromosome in female mammals (XX) compensates for the reduced dosage of X-linked gene expression in males (XY). However, the inner cell mass (ICM) of mouse preimplantation blastocysts and their in vitro counterparts, pluripotent embryonic stem cells (ESCs), initially maintain two active X chromosomes (XaXa). Random X chromosome inactivation (XCI) takes place in the ICM lineage after implantation or upon differentiation of ESCs, resulting in mosaic tissues composed of two cell types carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
(92 reference statements)
1
9
0
2
Order By: Relevance
“…Therefore, although the situation appears to be controversial, the latter is consistent with earlier studies demonstrating that XIST expression in human embryos is detectable by RT-PCR in both sexes at the blastocyst stage (Daniels et al 1997, Ray et al 1997. Another study in the rhesus monkey demonstrated that, based on RT-PCR not RNA-FISH, XIST is expressed not only from both X chromosomes in females but also from a single X in males at the blastocyst stage (Tachibana et al 2012). In addition, X-liked G6PD was apparently coexpressed with XIST, suggesting that XIST RNA expressed in the blastocyst had not yet induced silencing in the rhesus monkey.…”
Section: R134 T Sado and T Sakaguchisupporting
confidence: 82%
“…Therefore, although the situation appears to be controversial, the latter is consistent with earlier studies demonstrating that XIST expression in human embryos is detectable by RT-PCR in both sexes at the blastocyst stage (Daniels et al 1997, Ray et al 1997. Another study in the rhesus monkey demonstrated that, based on RT-PCR not RNA-FISH, XIST is expressed not only from both X chromosomes in females but also from a single X in males at the blastocyst stage (Tachibana et al 2012). In addition, X-liked G6PD was apparently coexpressed with XIST, suggesting that XIST RNA expressed in the blastocyst had not yet induced silencing in the rhesus monkey.…”
Section: R134 T Sado and T Sakaguchisupporting
confidence: 82%
“…Monkey ESC colonies are usually propagated by manual dissociation to small cell clusters 13,44 rather than single cells, as enzymatic treatment results in dramatic decrease in plating efficiency (< 1%) 13 . However, to enrich haploid cells, monkey PG-haESCs should be disaggregated into single cells for FACS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in these species, XIST was not imprinted, and both X chromosomes remained active in the ICM and TE of blastocysts. In addition, several studies found that the paternal X chromosome does not undergo imprinted X inactivation in human embryos and in extra-embryonic tissues (Skuse et al, 1997; Skuse, 2005; Moreira de Mello et al, 2010; Penaherrera et al, 2012; Tachibana et al, 2012). Similarly, XCI does not occur in bovine blastocysts.…”
Section: Introductionmentioning
confidence: 99%